Study on incidence of anoestrus and blood biochemical constituents in non cyclic and cyclic crossbred cows - YADAV, Y P; SINGH, A P; KUNJ, VIVEK; AKHTAR, M H; ROY, G P; SINGH, C (The Indian Journal of Animal Reproduction, 2023)
Incidence of anoestrus in crossbred cows (263) having reproductive disorder was studied during different seasons brought to the outdoor clinic of Gynaecology department of Bihar Veterinary College, Patna. The data showed the non-significant effect of season and month on anoestrus condition in cows. Overall percentage of anoestrus cows was found to be 30.42%. The highest incidence (47.62%) was recorded in March and lowest (14.28%) in May. During the study IO normal cycling and 30 anoestrus cows were selected randomly for study of biochemical profile blood glucose and serum alkaline phosphatase from the blood sample collected on 0,15th and 30th day . The observation revealed that significant difference (P<0.05) was found in serum calcium, serum inorganic phosphorus, total serum protein and blood glucose level between cycling and non-cycling crossbred cows. Alkaline phosphatase level did not differ significantly between cyclic and non cycling animals. The incidence of anoestrus cows was observed to be major factors responsible for infertility in . cows and it was independent of the effects of season and months.